1974
DOI: 10.1055/s-0028-1097918
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Pharmaco–toxicological Studies of Judaicin, Isolated From Artemisia Judaica

Abstract: W e investigated the digitalis like potentialities of judaicin in rats. Both the pharmacologic and the toxic actions of jtzdaicin and digoxin were studied in respect to the cardiac response. The pharmacological action as well as the cardiotoxic action of both drugs were electrocardiographically parallel. Both drugs caused a prolongation in the P-R interval and enforcement of the cardiac contractility.Further investigations are required for completing the picture of the pharmacological action of judaicin.For ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Concerning the isolated pure compounds, piperitone and trans-ethyl cinnamate showed pronounced insecticidal and antilarval activity against Spodoptera littoralis [ 22 ]. A sesquiterpene lactone known as judaicin exhibited a cardio-tonic effect slightly better than digoxin [ 23 ]. Another compound that was later identified as cirsimaritin demonstrated antioxidant, anticancer, anti-inflammatory, antimicrobial, antagonistic, antidiabetic, neurological, cardiovascular, and hepatoprotective activities [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the isolated pure compounds, piperitone and trans-ethyl cinnamate showed pronounced insecticidal and antilarval activity against Spodoptera littoralis [ 22 ]. A sesquiterpene lactone known as judaicin exhibited a cardio-tonic effect slightly better than digoxin [ 23 ]. Another compound that was later identified as cirsimaritin demonstrated antioxidant, anticancer, anti-inflammatory, antimicrobial, antagonistic, antidiabetic, neurological, cardiovascular, and hepatoprotective activities [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Artemisia species (Compositae) are known for their antibacterial, anthelmintic, antiinflammatory, stimulatory and antispasmodic activities (1)(2)(3)(4). The interperitoneal administration of santonin, one of the major compounds isolated from these plants (3) was found to cause a sig nificant antipyretic effect in rats (5).…”
mentioning
confidence: 99%
“…These bioactivities could be attributed to the plant’s phytochemicals. A. judaica accumulates volatile oil, sesquiterpene lactones, and phenolic compounds ( Galal et al, 1974 ; Abdelgaleil et al, 2008 ; Janaćković et al, 2015 ). Recent phytochemical research by LC/MS/MS showed that A. judaica possessed a plethora of flavonoids, phenolic acids, and terpenoids ( Goda et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%